Effect of marination with broccoli (Brassica oleracea var. italica) juice and soy sauce on physicochemical, structural and oxidative properties of beef steak - Ashkan Jebelli Javan; Fatemeh Mirhaj; Nasim Khorshidian; Mehrdad Mohammadi (Applied Food Research)
Softer and juicier meat is widely preferred and different ingredients have been used for marination of meat and improving its tenderness. This study aimed to investigate the effects of broccoli (Brassica oleracea var. Italica) juice and soy sauce on physicochemical properties, structural and oxidative stability of beef semitendinosus steaks. Samples were marinated with broccoli crude juice (15 mL v/w, 16.9 U/g) and soy sauce (25 mL v/w) individually and in combination and refrigerated at two different ageing times (1 and 48 h). The combined treatment showed higher pH, yellowness, thiobarbituric acid reactive substances (TBARS), myofibrillar fragmentation index, and total soluble protein compared to the control group (P < 0.05, 48 h). Lower brightness and redness were observed in marinated samples on the last day of storage (P < 0.05). Strong linear correlations were also found have between water holding capacity versus pH, myofibrillar fragmentation index versus total soluble protein. Moreover, some small peptides and short myofibrillar fractions with molecular mass between 20 and 30 kDa were detected by gel electrophoresis. In conclusion, using broccoli juice in combination with soy sauce is a safe and inexpensive marinade that can improve the tenderness of beef steaks.